2011
DOI: 10.1007/s13277-011-0281-3
|View full text |Cite
|
Sign up to set email alerts
|

Cellular changes in the tumor microenvironment of human esophageal squamous cell carcinomas

Abstract: The growth, invasiveness, and metastasis of human cancers are not only determined by the cancer cells but also by their microenvironment. The purpose of this study was to extend our previous studies and to examine the cellular changes in tumor microenvironment (stroma) of esophageal squamous cell carcinomas (ESCCs). The proliferative activity, cellular components, and angiogenesis status in different compartments (non-tumor stroma, tumor stroma, and tumor periphery stroma) of ESCCs were evaluated by immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Oesophageal SCC exhibit changes in stromal cell density shown to be increased in the peripheral tumour stroma when compared with stroma between tumour nests. The same study also showed that significantly higher SMA positive myofibroblasts which exhibited higher proliferative capacity correlated with tumour size (Liu, Li et al 2012). Studies on initiated, pre-malignant epithelial cells indicate that neoplastic growth is not necessarily stimulated when cultured with normal fibroblasts even under ideal conditions.…”
Section: Caf and Stromal Compositionmentioning
confidence: 78%
“…Oesophageal SCC exhibit changes in stromal cell density shown to be increased in the peripheral tumour stroma when compared with stroma between tumour nests. The same study also showed that significantly higher SMA positive myofibroblasts which exhibited higher proliferative capacity correlated with tumour size (Liu, Li et al 2012). Studies on initiated, pre-malignant epithelial cells indicate that neoplastic growth is not necessarily stimulated when cultured with normal fibroblasts even under ideal conditions.…”
Section: Caf and Stromal Compositionmentioning
confidence: 78%
“…Several reports have indicated an important role for infiltrative monocyte chemotactic protein-1 (MCPs) in cancer development and stated that tumor-associated macrophage (TAM) infiltration was found to be closely correlated with poor outcomes in several types of human malignancies [4,5,6,7]. In lung cancer, pancreatic cancer, and glioma, CD204 + macrophages infiltrate around the tumor and contribute to progression.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the number of Ki-67-positive cells (potential marker of tumor growth activity; refs. 44,45) and the MEMRI signal were decreased at 24 hours after irradiation (Fig. 5F).…”
Section: Factors Involved In Mnmentioning
confidence: 91%